2016
DOI: 10.1039/c6cc06015c
|View full text |Cite
|
Sign up to set email alerts
|

Surface-independent one-pot chelation of copper ions onto filtration membranes to provide antibacterial properties

Abstract: Surface-independent one-pot chelation of copper ions onto filtration membranes to provide antibacterial properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…The atomic fraction of copper element in the surface coating of Cu-modified PVC is 1.5% (Table 2), which is close to the reported 1.4% on polysulfone and 1.36% on polyvinydienefluoride ultrafiltration membranes [38]. In case of Cu modified PU, there is much less Cu detected than expected from other experimental results.…”
Section: Colloids Interfaces 2019 3 X For Peer Review 6 Of 13supporting
confidence: 84%
“…The atomic fraction of copper element in the surface coating of Cu-modified PVC is 1.5% (Table 2), which is close to the reported 1.4% on polysulfone and 1.36% on polyvinydienefluoride ultrafiltration membranes [38]. In case of Cu modified PU, there is much less Cu detected than expected from other experimental results.…”
Section: Colloids Interfaces 2019 3 X For Peer Review 6 Of 13supporting
confidence: 84%
“…Inspired by this, we reasoned that DA/PEI co-deposition might form a much denser and more hydrophilic network to better 'seal' the enzymes in the membrane support. On the other hand, the addition of copper ions could also accelerate DA polymerization even at acidic pH [25][26][27]. Additionally, it has been found that the nano-coppers could facilitate the electron transfer in the catalytic reaction of 2,4,6-Trichlorophenol by laccase [28], hence we hypothesize DA/Cu 2+ co-deposition may benefit laccase activity and micro-pollutants removal.…”
Section: Introductionmentioning
confidence: 78%
“…Especially for the DA/PEI co-deposition, this kind of coating layer could even be used for NF membrane fabrication after cross-linking [24], implying that the PDA/PEI layer was dense enough to 'seal' the enzyme in the membrane. Besides the higher enzyme loading, the PDA/PEI and PDA/Cu 2+ coatings also showed better anti-bacterial properties compared with the single PDA coating because PEI molecules and copper ions carried antibacterial ability [27,32]. As seen in Fig.…”
Section: Enzyme Loading Activity and Permeability Of Biocatalytic Mementioning
confidence: 90%
See 2 more Smart Citations